Penggunaan Metode Delone dan Mclean Untuk Menganalisis Kesuksesan Mulawarman Online Learning System (MOLS) - Setyaningtyas, Adella Ayu; Jundillah, Muhammad Labib; Kamila , Vina Zahrotun (Adopsi Teknologi dan Sistem Informasi (ATASI), 2023)
In 2019, the Mulawarman Online Learning System (MOLS) was created. All Mulawarman University students can use MOLS for support their study. The purpose of this reasearch is to determine the level of success in using the Mulawarman Online Learning System (MOLS) using the Delone and Mclean method. In this study using the Delone and Mclean method. Delone and Mclean are methods for measuring the success rate of users of an information system. Delone and Mclean have 6 (six) measurement variables including system quality, information User Satisfaction Delone and Mclean E-Learning quality, user satisfaction, use, service quality and net benefit. This research is quantitative data with a sample of 100 Mulawarman University student respondents. The results of this study indicate that the independent variables, namely system quality, information quality and service quality can affect the dependent variable, namely user satisfaction, use and net benefits.